Industrial investment is the key to economic prosperity - Pulatova Mokhira Bakhtiyorovna (Peerian Journals Publishing, 2023)
Industrial enterprises are the most reliable and profitable assets for investment. By investing in them, investors develop the real sector of the economy and receive embodied assets in the form of property and profits of the industry's flagships. International extraction of valuable resources continues to grow rapidly every year.
Keywords: Industrial enterprises